Thermo-Optical Characterization of Therminol55 Based MXene–Al2O3 Hybridized Nanofluid and New Correlations for Thermal Properties - Likhan Das; Khairul Habib; Kashif Irshad; Rahman Saidur; Salem Algarni; Talal Alqahtani (Nanomaterials, 2022)
The current research focuses on formulating a new class of Therminol55-based nanofluids that incorporates an MXene/Al2O3 nanocomposite as the new class of dispersant at three different concentrations of 0.05, 0.10, and 0.20 wt%. The optical and thermophysical properties of the formulated nanofluid are assessed experimentally. Zeta potential and FTIR analyses are employed to evaluate the composite particles' surface charge and chemical stability, respectively. Thermal conductivity is observed to increase with nanoparticle loading and maximally augmented by 61.8% for 0.20 wt%, whereas dynamic viscosity increased with adding nanoparticles but remarkably dropped with increasing temperature. In addition, the prepared TH55/MXene + Al2O3 samples are thermally stable up to 200 °C according to TGA analyses. Moreover, the proposed correlations for the thermal conductivity and viscosity showed good agreement with the experimental data. The study’s findings suggest that the formulated nanofluid could be a viable contender to be used as a heat transfer fluid in the thermal sector.